2009
DOI: 10.1007/s10452-009-9286-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of road salts on the composition of seasonal pond communities: can the use of road salts enhance mosquito recruitment?

Abstract: Road deicing agents can enter nearby wetlands and alter the composition of aquatic communities by directly eliminating salt-intolerant species and modifying ecological interactions between tolerant species. We conducted field experiments to examine the sensitivity of taxa that inhabit seasonal wetlands and to determine whether salt contamination could increase the production of ovipositing insects. In two outdoor mesocosm experiments, cladocerans and copepods rarely survived concentrations of commercial road s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
59
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 34 publications
7
59
6
Order By: Relevance
“…A total of 131 species have been recorded and/or examined as adults, 75 as larvae, and only 35 as eggs. There is some apparent consensus in the literature that amphibian embryos are most sensitive to salt, followed by larvae, with adults being most tolerant (Gordon et al 1961;Roberts 1970;Beebee 1985;Padhye and Ghate 1992;Chinathamby et al 2006;Brand et al 2010;Petranka and Doyle 2010;Bernabò et al 2013;Hopkins et al 2014;Thirion 2014), although there are also some dissenting data and evidence that sensitivity can also change with age within a particular life stage (see Alexander et al 2012). This may be due to differences in the physiological abilities and mechanisms of different life-history stages to regulate salt.…”
Section: Degree Of Understandingmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 131 species have been recorded and/or examined as adults, 75 as larvae, and only 35 as eggs. There is some apparent consensus in the literature that amphibian embryos are most sensitive to salt, followed by larvae, with adults being most tolerant (Gordon et al 1961;Roberts 1970;Beebee 1985;Padhye and Ghate 1992;Chinathamby et al 2006;Brand et al 2010;Petranka and Doyle 2010;Bernabò et al 2013;Hopkins et al 2014;Thirion 2014), although there are also some dissenting data and evidence that sensitivity can also change with age within a particular life stage (see Alexander et al 2012). This may be due to differences in the physiological abilities and mechanisms of different life-history stages to regulate salt.…”
Section: Degree Of Understandingmentioning
confidence: 99%
“…Gadow (1901) stated that ''Common salt is poison to the Amphibia,'' and there is no doubt that amphibians are indeed osmotically challenged organisms due to their permeable skin and eggs (Shoemaker and Nagy 1977). A plethora of studies have found that salt can lead to increased mortality, developmental deformities, physiological stress, and the alteration of growth and development at (e.g., Ely 1944;Ruibal 1959;Beebee 1985;Padhye and Ghate 1992;Viertel 1999;Turtle 2000;Chinathamby et al 2006;Dougherty and Smith 2006;Collins and Russell 2009;Karraker and Ruthig 2009;Langhans et al 2009;Chambers 2011;Duff et al 2011;Harless et al 2011;Alexander et al 2012;Hopkins et al 2013a,b;Hua and Pierce 2013) and across different life-history stages (i.e., carry-over effects; Petranka and Doyle 2010;Wu et al 2012;Hopkins et al 2014). This general intolerance has been demonstrated repeatedly (and as such will not be a focus of this review) and, perhaps as a result, there are no truly marine-or salinespecialist amphibian species.…”
mentioning
confidence: 99%
“…Both malathion and carbaryl have been shown to negatively impact zooplankton communities, apparently minimizing competitive interactions with tadpoles for limited algal food resources (Boone et al 2004;Relyea and Hoverman 2008, respectively). Petranka and Doyle (2010) found that road salts can alter seasonal pond communities in favor of salt tolerant insects such as mosquitoes, which may serve as competitors to larval amphibians and zooplankton. Therefore, complete understanding of the impact of any contaminant on aquatic communities requires an understanding of indirect effects.…”
Section: Introductionmentioning
confidence: 99%
“…On 24 January 2012, mesocosms (clear plastic storage containers, 67 by 40 cm, 30 cm in height) were established to replicate many factors associated with natural wetland ecosystems. Such mesocosms are within the size ranges used in other noncontainer breeding mosquito mesocosm studies (Carver et al 2009, Petranka andDoyle 2010); however, we are aware that our mesocosms might also be suitable for incidental oviposition by container breeding species. In this region, wetlands in both natural and agricultural landscapes are generally Ͻ1 ha (Martin et al 2011).…”
Section: Methodsmentioning
confidence: 91%